STUDYING THE FREQUENCY OF INCIDENCE, CLINICAL AND NEUROLOGICAL FEATURES AND THE POSSIBILITY OF DIAGNOSTIC METHODS FOR KIMMERLE ANOMALY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The frequency of occurrence of variants of the development of the structure of cerebral vessels inpatients with Kimmerle anomaly was studied. 67 patients with Kimmerle anomaly wereexamined, aged from 16 to 60 years, average age 40±5 years; 55 women – 82.0% and 12 men –18%. All subjects underwent MSCT of the brain with capture and 3D craniovertebral junctionand MR angiography. Correlative data of radiological and clinical signs were determined withsubsequent statistical processing. It has been determined that in most cases with Kimmerle'sanomaly there are anomalies in the development of cerebral vessels.